Hospital Safety Box Monitoring: Building Brand Trust in Healthcare Business During Covid -19 Wave - Johansyah, Muhamad Deni; Purnama, Susan (iora, 2021)
The health business is adjusting to a new reality where bargaining power has shifted to consumers. Consumers are now playing a key role in the commercialization process, making them important stakeholders to fulfill their needs. Health business reforms have convinced consumers to give protection a greater priority than ever since the COVID-19 pandemic escalated around the world. Health care businesses in Indonesia are no exception, should increase their brand trust, because of the huge responsibility to protect consumers from the prevention of COVID-19, and brand trust also gives added value to the hospital's own brand. A brand with the right value proposition can